2009
DOI: 10.1159/000229024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Therapy on Anxiety and Depression in Patients with Alzheimer’s Type Dementia: Randomised, Controlled Study

Abstract: Background/Aims: Numerous studies have indicated the value of music therapy in the management of patients with Alzheimer’s disease. A recent pilot study demonstrated the feasibility and usefulness of a new music therapy technique. The aim of this controlled, randomised study was to assess the effects of this new music therapy technique on anxiety and depression in patients with mild to moderate Alzheimer-type dementia. Methods: This was a single-centre, comparative, controlled, randomised study, with blinded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(160 citation statements)
references
References 44 publications
1
149
3
7
Order By: Relevance
“…Psychosocial interventions, such as psychotherapy, music therapy, reminiscence therapy, and physical training programs, should be implemented in nursing homes at a larger scale. However, so far only a few studies have explored the efficiency of nonpharmacological treatment [7,40,41], and comparative studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial interventions, such as psychotherapy, music therapy, reminiscence therapy, and physical training programs, should be implemented in nursing homes at a larger scale. However, so far only a few studies have explored the efficiency of nonpharmacological treatment [7,40,41], and comparative studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Music has many therapeutic benefits for people with dementia (Gu etin et al, 2009;Ray & Fitzsimmons, 2014). Although it cannot cure dementia, it has been shown to decrease behavioral problems (Ray & Fitzsimmons, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This calming effect allows caregivers to feel more comfortable and enables them to better communicate with the patients. Patients with Alzheimer's disease were found to benefit from MT for reducing anxiety levels [48,49]. In several other studies examining the effect of MT on anxiety and agitated behaviors in patients with dementia, the authors found a significant reduction in both anxiety and agitated behaviors after MT [49,50,51,52,53].…”
Section: Discussionmentioning
confidence: 99%